Tacaco (Sechium tacaco; Cucurbitaceae): quantification of the variability in the number of spines and sutures of the fruit (UNED Research Journal, 2024)
Introduction: The fruits of tacaco, Sechium tacaco, a plant endemic to Costa Rica, are primarily consumed as a vegetable or dessert, and few studies have addressed the morphological variability of these fruits. Objective: To quantify the variability in the number of spines and longitudinal sutures of the fruit. Methods: We collected 6-90 fruits from each of 22 tacaco accessions, between 2013 and 2019. We evaluated longitudinal sutures and number of spines. Results: For 20 accessions, the mode was five complete longitudinal sutures.  For incomplete longitudinal sutures, the modes were zero (8 accessions), one (6 accessions) and two (6 accessions). For total number of longitudinal sutures, 10 accessions had a mode of six and 10 accessions a mode of seven.  For fruits with spines, six accessions had 15-19 spines per fruit, and four accessions 20-24 spines per fruit. Conclusion: The phenotypic variability in spines and longitudinal sutures, suggests that these characteristics are controlled by multiple genes, indicating a polygenic inheritance; this variability could be key for genetic improvement and conservation of the diversity of this species.
Keywords: Cucurbitaceae; Costa Rica; Central America; diversity; vegetable